2000
DOI: 10.1086/316915
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in FOXC2 (MFH-1), a Forkhead Family Transcription Factor, Are Responsible for the Hereditary Lymphedema-Distichiasis Syndrome

Abstract: Lymphedema-distichiasis (LD) is an autosomal dominant disorder that classically presents as lymphedema of the limbs, with variable age at onset, and double rows of eyelashes (distichiasis). Other complications may include cardiac defects, cleft palate, extradural cysts, and photophobia, suggesting a defect in a gene with pleiotrophic effects acting during development. We previously reported neonatal lymphedema, similar to that in Turner syndrome, associated with a t(Y;16)(q12;q24.3) translocation. A candidate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
367
0
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 535 publications
(378 citation statements)
references
References 25 publications
6
367
0
5
Order By: Relevance
“…Interestingly, previous research in Foxc2 −/− mice also showed an abnormal amount of SMCs surrounding enlarged lymph vessels (Petrova et al, 2004). Mutations in the human FOXC2 gene are associated with congenital lymphedema and defective lymph valves (Fang et al, 2000). FOXC2 normally suppresses the expression of plateletderived growth factor (PDGF)-B in lymphatic endothelial cells, thereby inhibiting SMC attraction and proliferation, as these processes are positively influenced by PDGF-B (Lindahl et al, 1997;Petrova et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, previous research in Foxc2 −/− mice also showed an abnormal amount of SMCs surrounding enlarged lymph vessels (Petrova et al, 2004). Mutations in the human FOXC2 gene are associated with congenital lymphedema and defective lymph valves (Fang et al, 2000). FOXC2 normally suppresses the expression of plateletderived growth factor (PDGF)-B in lymphatic endothelial cells, thereby inhibiting SMC attraction and proliferation, as these processes are positively influenced by PDGF-B (Lindahl et al, 1997;Petrova et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The gene for LD, located on the long arm of chromosome 16, is that encoding FOXC2, a forkhead family transcription factor involved in numerous developmental pathways. 13 In all three members of the family presented in this report, a 19 bp insertion in the FOXC2 gene was identified. To our knowledge this mutation has not been previously reported.…”
mentioning
confidence: 69%
“…Mice heterozygous for both Foxc2 and Vegfr3 display a phenotype very similar to Foxc2 ¡/-mice, suggesting that FOXC2 and VEGFR-3 act through a common genetic pathway to establish some of the distinct properties of the lymphatic vasculature. The human disease lymphedema-distichiasis (LD), an autosomal dominant disease, is caused by heterozygousloss-of-function mutations of Foxc2 (Fang et al 2000). Unlike in congenital lymphedema, the lymphatic vasculature in LD is normal or hyperplastic, but there is lymph backXow, presumably due to abnormal lymphatic valves, defective patterning and the presence of ectopic SMCs (Brice et al 2002;Petrova et al 2004).…”
Section: Maturation Of the Lymphatic Vasculaturementioning
confidence: 99%
“…This model has been used to test VEGF-C gene therapy, which promoted the formation of functional lymphatic vessels in these mice. In the case of lymphedema-distichiasis (LD, OMIM 153400), mutations in the forkhead transcription factor FOXC2 have been identiWed (Fang et al 2000;Finegold et al 2001). This disorder is characterized by distichiasis (a double row of eyelashes) at birth and bilateral lower limb lymphedema at puberty.…”
Section: Pathology Of Lymphatic Vesselsmentioning
confidence: 99%